Developing A Course Book of F&B Service for Enhancing Instruction in Tourism Class - Dewa Ayu Made Juli Astari; I. B. Arya Lawa Manuaba; I Putu Suyoga Dharma; I Putu Mariana (Universitas Pendidikan Ganesha, 2021)
The purpose of this research is to develop a product and this research uses the research and development method level I from Sugiyono (2019). The steps in developing this research are (1) Potential and problems (2) Literature study (3) Gathering information (4) Design product (5) validate product (6) Design is assessed. The instruments used in this research were observations sheet, lists of interview, and questionnaires. The observation sheet was used to observe the needs and problem that facing by the vocational school students. The lists of the interview were used to make sure the needs of teachers and students. And the questionnaire was used for product validation/product valuation by experts. Based on the recapitulation of experts’ judgment validation, it showed that the developing course book of food and beverage services obtained the best category with score 116 obtained from the first expert, 120 obtained from the second expert, and 123 obtained from the third expert, so the mean score is 119,6. It can be concluded that the mean score is greater than 104.88 with the best category, so the material developed is valid or gets the best category and suitable for students, but there are some points that must be revised based on comments from experts